3. Practice Through Movement and Practice Through Motionlessness - Leșe Ana-Cristina (Sciendo, 2018)
Through this paper we address the students from theatre and music specialists, but also all people interested in elements belonging to Tai Chi practice, considering that these, once introduced into a specific physical exercise program, are beneficial for the development of the respiratory capacity and also for a good physical and mental balance that support the professional skills. These two expressions used in the majority of martial arts, dung-gong movement practice and jing-gong motionless practice are yin and yang aspects and are based on the balance between motion and stillness of the body and the mind.